Isolated Gastrocnemius Recession for Plantar Fasciitis. Issue 3 (14th September 2018) - Cheney, Nicholas; Law, Timothy; Zehnder, David; Large, Bryan; Rockwell, Kyle; Whitehead, Brent; Vazquez, Mckinly
Category: Hindfoot Introduction/Purpose: Plantar fasciitis is a debilitating problem that can cause long-term pain. Multiple different studies with various modalities have been suggested to treat the inflammation of the plantar fascia. None of them have provided a cause for the inflammation. A few recent studies have shown gastrocnemius equinus to be a driving factor in foot pain, which includes plantar fasciitis. Our belief is that the inflammation is due to a stretch placed on the plantar fascia due to a gastrocnemius equinus contracture and the beginning of an arch collapse per the Grand Rapids arch collapse model. As such, we wanted to review our results with an isolated gastrocnemius recession for the treatment of plantar fasciitis. Methods: We retrospectively reviewed patient data collected by isolating ICD-9 and ICD-10 codes for plantar fasciitis. These patients presented to the senior author's office with a complaint of plantar heel pain, were diagnosed with a gastrocnemius equinus contracture and plantar fasciitis, failed conservative treatment, and opted for an isolated gastrocnemius recession as a definitive treatment of the fasciitis. From the timeframe of 1/1/2015 to 6/12/17, there were 68 out of 97 patients who qualified for the study based on the necessary criteria: an initial consultation pain score, initial post-operative pain score at two weeks, and second post-operative pain score at eight weeks. These patients did not have coexisting surgeries at the time of the gastrocnemius recession or prior surgery to the area in discussion. Results: For the 68 patients (five of which underwent bilateral procedures at a minimum of six weeks apart), who elected to have a gastrocnemius recession for plantar fasciitis, the average initial presenting pain was a 7.4 on a scale of 0 to 10. The average initial post-operative pain score was 2.8 and the average second post-operative pain score was 3.3. The average number of days from initial to second post-operative appointment was 136 days. Of the 68 patients, 21 returned after their eight-week post-operative visit for evaluation. Only 3 returned with recurrent plantar heel pain, 4 more presented with new onset tarsal tunnel syndrome, three more with heel pain different from their pre operative pain and the remaining patients had new onset unrelated pain. Conclusion: We have demonstrated that an isolated gastrocnemius recession can decrease the pain score in patients with recalcitrant plantar fasciitis. Follow up care beyond eight weeks post operation is not routinely performed due to the limited nature of the procedure. The improvement demonstrated in the VAS scores of the patients included in this study show a definite improvement and as such, we believe that an isolated gastrocnemius recession should be considered as a definitive treatment of plantar fasciitis. Future prospective randomized studies will need to be completed to further evaluate the effectiveness of this procedure.